Pengaruh Kompensasi dan Komitmen Organisasi Melalui Motivasi Kerja Terhadap Kinerja Karyawan PT Penta Valent Jambi - M Iman Khoeruman; Sayid Syekh; Susilawati Susilawati (J-MAS (Jurnal Manajemen dan Sains), 2018)
This research aims to know the influence of organizational commitment Through compensation and Motivation of work on performance of employees of PT Penta Valent-Jambi. The diginakan method in the research of using path analysis (path analysis). Results of the study prove that compensation and organizational commitment to simultaneously effect positively and significantly to the motivation of working employees at PT Penta Valent-Jambi. Where the total direct and indirect influence of the compensation and the commitment of the Organization together against the motivation of 52.4%, where the figure explains that directly compensation and organizational commitment to contribute against the work motivation of 52.4%, while the rest of 47.6% is affected by other variables that are not included in this model. Keywords: compensation, commitment, motivation, employee performance